Identification of Two Novel Candidate Genetic Variants Associated With the Responsiveness to Influenza Vaccination - Wen, Simin; Wei, Hejiang; Liao, Qijun; Li, Mao; Zhong, Shuyi; Cheng, Yanhui; Huang, Weijuan; Wang, Dayan; Shu, Yuelong (Frontiers in Immunology, 2021)
Background: Annual vaccination is the most effective prevention of influenza infection. Up to now, a series of studies have demonstrated the role of genetic variants in regulating the antibody response to influenza vaccine. However, among the Chinese population, the relationship between genetic factors and the responsiveness to influenza vaccination has not been clarified through genome-wide association study (GWAS). Method: A total of 1968 healthy volunteers of Chinese descent were recruited and 1582 of them were available for the subsequent two-stage analysis. In the discovery stage, according to our inclusion criteria, 123 of 1582 subjects were selected as group 1 and received whole-genome sequencing to identify potential variants and genes. In the verification stage, 29 candidate variants identified by GWAS were selected for further validation in 481 subjects in group 2. Besides, we also analyzed 9 variants from previously published reports. Results: Multivariate logistic regression analysis showed that compared with the TT genotype of ZBTB46 rs2281929, the TC+CC genotype was associated with a lower risk of low responsiveness to influenza vaccination adjusted for gender and age (Group2: P=7.75E-05, OR=0.466, 95%CI=0.319-0.680; Combined group: P=1.18E-06, OR=0.423, 95%CI=0.299-0.599). In the combined group, IQGAP2 rs2455230 GC+CC genotype was correlated with a lower risk of low responsiveness to influenza vaccination compared with the GG genotype (P=8.90E-04, OR=0.535, 95%CI=0.370-0.774), but the difference was not statistically significant in group 2 (P=0.008). The antibody fold rises of subjects with ZBTB46 rs2281929 TT genotype against H1N1, H3N2 and B were all significantly lower than that of subjects with TC+CC genotype (P<0.001). Compared with IQGAP2 rs2455230 GC+CC carriers, GG carriers had lower antibody fold rises to H1N1 (P=0.001) and B (P=0.032). The GG genotype of rs2455230 tended to be correlated with lower antibody fold rises (P=0.096) against H3N2, but the difference was not statistically significant. No correlation was found between 9 SNPs from previously published reports and the serological response to influenza vaccine. Conclusion: Our study identified two novel missense variants, ZBTB46 rs2281929 and IQGAP2 rs2455230, were associated with the immune response to influenza vaccination among the Chinese population. Identifying these variants will provide more evidence for future research.